2018
DOI: 10.1136/sextrans-2018-053583
|View full text |Cite
|
Sign up to set email alerts
|

Usage of purchased self-tests for HIV infections among migrants living in the UK, France and the Netherlands: a cross-sectional study

Abstract: HIVST usage among migrants from the UK, France and the Netherlands was relatively low between 2014 and 2015 but higher among migrant MSM. To increase HIV testing rates among migrants, programmes need to be developed to promote HIVST among this group. Also, as more countries approve usage of HIVST, systems need to be established to ensure linkage to confirmatory testing and care following a positive test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Free and easy to access self-tests could also lower the barrier for stigma among several risk groups [ 30 ]. In addition, HIV awareness on early testing in disproportionately affected subgroups should be increased among general practitioners and other healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free and easy to access self-tests could also lower the barrier for stigma among several risk groups [ 30 ]. In addition, HIV awareness on early testing in disproportionately affected subgroups should be increased among general practitioners and other healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore migrants are placed at risk of poor HIV related clinical outcomes [29]. In order to reach this unaware population more aggressive testing could be performed by for example HIV indicator condition testing or implement the distribution of HIV self-tests [30][31][32].…”
Section: Plos Onementioning
confidence: 99%
“…HIV self-testing (HIVST) enables people to test for HIV conveniently and privately and is a promising tool to improve HIV testing uptake among migrant GBMSM ( 27 , 28 ). Studies from several countries have confirmed that access to HIVST kits increases HIV testing uptake and frequency among GBMSM ( 29 32 ).…”
Section: Introductionmentioning
confidence: 99%